Foreign Accents in Polish: Non-native Speakers’ and Native Listeners’ Views - Szpyra-Kozłowska, Jolanta; Radomski, Marek (Research in Language, 2013)
As in recent years a growing number of foreigners have been settling in Poland and learning our language, Poles have found themselves in a fairly new situation of being increasingly exposed, both in direct contacts and through the media, to their mother tongue pronounced with a variety of foreign accents. In a series of studies (SzpyraKozłowska and Radomski 2012, in press, Szpyra-Kozłowska 2013b) we have undertaken an examination of how such accents are perceived and evaluated by Polish listeners. The issues that have come under scrutiny so far concerned identification of the speakers’ origin, evaluation of different accents in terms of their intelligibility, degree of accentedness and acceptance, establishing the major perceptual properties of several accents and examining their salience. In the present paper we focus on the participants of communication which involves accented Polish, i.e. non-native speakers and native listeners, and their views on this phenomenon. We examine them in two questionnaire studies, one administered to 40 foreign learners of Polish and the other one to 80 native listeners. Thus, our study sets itself the following goals: to examine what attitudes Poles take towards Polish-speaking foreigners and their accents in particular (Questionnaire 2); to juxtapose these opinions with foreign learners’ experience of Poles’ reactions to accented Polish (Questionnaire 1); to draw implications for the phonetic training of foreigners who undertake to learn Polish.